2014
DOI: 10.4314/njbas.v22i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Characterization of Extracellular Protease from <i>Pedicoccus acidilactici</i>

Abstract: Microbial proteases have wide industrial applications and proteases of the lactic acid bacteria (LAB) have received special attention because of their importance in the food and dairy industry. Of all the LAB, the proteolytic system of the pediococci is the least studied. Therefore, this study was aimed at characterizing and purifying the protease produced by Pediococcus acidilactici grown in de Man, Rogosa and Sharpe (MRS) broth. Casein concentration of 2% (w/v) and 2.5 ml of the crude enzyme were optimal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…The proteinase produced by a proteolytic strain of P. acidilactici has been studied previously. The results showed that the proteinase was an acidic proteinase [37], and this confirmed the result that P. acidi lactici contributed to the proteolysis in both mature TMR silages with pH values of approximately 4.2 in this experiment. Proteoyltic activities of genus Enterococci were mainly described in milk products.…”
supporting
confidence: 88%
“…The proteinase produced by a proteolytic strain of P. acidilactici has been studied previously. The results showed that the proteinase was an acidic proteinase [37], and this confirmed the result that P. acidi lactici contributed to the proteolysis in both mature TMR silages with pH values of approximately 4.2 in this experiment. Proteoyltic activities of genus Enterococci were mainly described in milk products.…”
supporting
confidence: 88%
“…This value falls within the range of molecular mass of 45-55 kDa which was obtained in this study. In addition, the submissions of [92][93][94] confirmed the results obtained in this study.…”
Section: Purification Of Crude Proteasesupporting
confidence: 86%